2014
DOI: 10.1016/j.jcsr.2014.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of axially loaded circular concrete-filled stainless steel tubular short columns

Abstract: Experiments show that the ultimate compressive strength of stainless steel is much higher than its tensile strength. The full-range two-stage constitutive model for stainless steels assumes that stainless steels follow the same stress-strain behavior in compression and tension, which may underestimate the compressive strength of stainless steel tubes. This paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…There are two options to model the interaction between the U-shaped steel and the in-filled concrete. First, the bond between the steel and concrete is considered perfect and no slip occurs, which was employed in past research [33][34][35]. Second, the interaction between the steel and concrete is simulated by using spring elements and contact elements [36,37].…”
Section: Finite-element Modelsmentioning
confidence: 99%
“…There are two options to model the interaction between the U-shaped steel and the in-filled concrete. First, the bond between the steel and concrete is considered perfect and no slip occurs, which was employed in past research [33][34][35]. Second, the interaction between the steel and concrete is simulated by using spring elements and contact elements [36,37].…”
Section: Finite-element Modelsmentioning
confidence: 99%
“…Patel et al [46] reported that there are significant differences between assuming the same and different strain hardening characteristics in tension and compression of stainless steel materials. Their study indicated that the average ultimate axial load of CFSST short columns was underestimated by about 16.9% by using the model that assumes the same strainhardening behavior in tension and compression when compared to that computed by the model assuming different strain hardening characteristics in tension and compression.…”
Section: Stainless Steelsmentioning
confidence: 99%
“…Quach et al [44] reported that stainless steel has different strain hardening characteristics in compression and tension [45] and the two-stage stress-strain laws given by Rasmussen [43] were based on the tension coupon test results, which underestimates the ultimate compressive strength of stainless steels. Patel et al [46] incorporated the accurate three-stage stress-strain relations given by Quach et al [44] and Abdella et al [47] for stainless steels in the fiber element modeling of short circular CFSST columns. The numerical solutions obtained were shown to agree well with experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…[12] experimentally analysed the strength and ductility indices for dune sand CFST members. In 2014 Patel [13] experimentally analysed the axial compression behaviour of circular CFSST columns, which showed an ultimate compressive strength of stainless steel higher than its tensile strength and derived the fibre model based on the threestage stress-strain relationship of stainless steel. In the same year Tam [14] carried out the experimentation and finite element simulation of CFSST short columns with regard to their diameter-thickness ratios.…”
Section: Introductionmentioning
confidence: 99%